2015
DOI: 10.1021/acs.joc.5b01504
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Intramolecular formal [4 + 2] Cycloaddition of Aryl-Substituted o-Vinylstyryl-2-oxazoles To Form Benzo[f]quinoline Derivatives: Experimental Results and Theoretical Interpretation

Abstract: A new approach to benzo[f]quinoline derivatives has been found by an effective formal [4 + 2] photocycloaddition process from novel aryl-substituted o-vinylstyryl-2-oxazoles. All of the o-vinylstyryl-2-oxazoles were synthesized by a multicomponent Wittig reaction from the diphosphonium salt of α,α'-o-xylene dibromide, formaldehyde, and 5-tolyl-, 4-phenyl-5-methyl-, and 4,5-diphenyloxazole-2-carbaldehydes. TD-DFT calculations revealed that the intramolecular photocyclization in 2-(2-vinylstyryl)oxazoles to form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 44 publications
0
19
0
2
Order By: Relevance
“…Scheme 1. [10][11][12][13] Examples of photochemical intermolecular cycloadditions that include oxazoles are numerous [14][15][16][17][18][19][20] but for the intramolecular photocycloaddition, to our knowledge, the only examples are those published by us for various substituted 2-(2-vinylstyryl)oxazoles [1] and the unsubstituted 4-and 5-(2-vinylstyryl)oxazoles. [1,2] derivatives.…”
Section: 1]octenonementioning
confidence: 99%
See 1 more Smart Citation
“…Scheme 1. [10][11][12][13] Examples of photochemical intermolecular cycloadditions that include oxazoles are numerous [14][15][16][17][18][19][20] but for the intramolecular photocycloaddition, to our knowledge, the only examples are those published by us for various substituted 2-(2-vinylstyryl)oxazoles [1] and the unsubstituted 4-and 5-(2-vinylstyryl)oxazoles. [1,2] derivatives.…”
Section: 1]octenonementioning
confidence: 99%
“…In our previous paper we described the synthesis of 2-(2-vinylstyryl)oxazoles, [1] which, upon irradiation, gave quinolines via oxo-bridged derivatives. The study of the 5-tolyl-, 4,5-diphenyland 4-phenyl-5-methyl-2-(2-vinylstyryl)oxazole showed that the phenyl substituent on the 4-position in the oxazole ring has a high impact on the overall electron density distribution in the molecule and on the photocyclization process (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…A different approach, to similar quinoline derivatives, based on a [4 + 2] photocycloaddition of o-vinylstyryl-2-oxazoles was described (15JOC9535). A modified Pictet-Spengler method that uses Cu(CF 3 COO) 2 as the catalyst allowed the elaboration of aryloxazoles 103 to obtain oxazoloquinolines 105.…”
Section: Oxazolesmentioning
confidence: 99%
“…[2] When properly functionalized, bicyclo[3.2.1]octanes have proved to be useful reactive intermediates in stereoselective transformations. [5] During our long-standing studies in photochemical intramolecular cycloaddition reactions of various -heteroaryl-o-divinylbenzenes such as furans, [6][7][8] thiophenes, [8][9][10] pyrroles, [11,12] sydnones, [13][14][15] and most recently oxazoles, [16][17][18] routes were obtained for a whole library of polycyclic compounds that include a vast number of structures with the benzobicyclo[3.2.1]octadiene moiety (A-D) (Scheme 1). [3,4] The benzobicyclo[3.2.1]octadiene skeleton can thus be even more useful, as it can easily be transformed by adding various functional groups to the isolated double bond.…”
Section: Introductionmentioning
confidence: 99%
“…For the first time, a study of efficiency was conducted where the efficiency of intramolecular cycloaddition of these heterocyclic butadiene derivatives was investigated by simultaneous use of ferrioxalate and valerophenone actinometers. From vast previous studies of the excited state behavior conducted on stilbene moieties, [7][8][9][10][11][12][13][14][15][16][17][18] it was expected that butadiene derivatives would give, by intramolecular photocycloaddition, a new line of polycyclic products. [19] Derivatives that have been investigated so far have been those with phenyl and 2-furyl substituents (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%